Chronic impact of reduced cerebral blood flow on synaptic structure and glial responses - Pilcher, Jemma Louise (The University of Edinburgh, 2020)
Vascular cognitive impairment (VCI) results from a heterogeneous range of cerebrovascular injuries, such as stroke, cerebral large and small vessel disease, or cerebral amyloid angiopathy, which reduce cerebral blood flow and starve brain cells of oxygen and nutrients needed for normal function. Blood flow reductions are central to VCI and can range from mild chronic hypoperfusion to severe issues such as focal ischemic stroke. Cerebrovascular pathology and blood flow reductions are also a feature of Alzheimer’s disease, which has considerable overlap with VCI. There are few therapeutic options to treat VCI, and they are limited by mechanistic insight. Synapse loss is considered to be the pathological feature that underpins cognitive decline in Alzheimer’s disease and dementia. In Alzheimer’s disease (AD), synaptic dysfunction is known to occur early in the disease progression and it is thought to be the result of synaptotoxicity caused by oligomeric forms of soluble β-amyloid, a central pathogenic feature of AD. Previous studies have found that severe reductions in cerebral blood flow (ischaemia) cause immediate synaptic and neuronal degeneration. However, there is limited understanding of the longer-term impact of ischaemia on synapses, and even less knowledge of whether more modest reductions of blood flow also cause alterations in synapses. Gaining a better understanding of those issues is important in determining how synaptic changes contribute to the spectrum of VCI, and whether there are common changes that may be targeted therapeutically. Glutamate is the main excitatory neurotransmitter in the brain. There is evidence that glutamatergic neurons and synapses are particularly vulnerable in a number of neurodegenerative conditions, including stroke and AD. Dendrites and axons, the neuronal processes that pre- and postsynaptic terminals project from, have also been found to be susceptible to degeneration in pathological conditions. The studies in this thesis, therefore, investigate the overarching hypothesis that a range of cerebral blood flow reductions causes a long-term loss of glutamatergic pre- and postsynaptic terminals culminating in VCI, and that the additional comorbidity of β-amyloid pathology will lead to worsened synapse loss and functional impairment. At the outset, the first aim was to assess the long-term effects of modest cerebral hypoperfusion on dendrites and glutamatergic pre- and postsynaptic terminals. Modest cerebral blood flow reductions were surgically induced in mice, by bilateral common carotid stenosis (BCAS). The densities of dendrites and glutamatergic pre- and postsynaptic terminals were measured with histological and immunohistochemical approaches in wild-type (WT) mice, 1 and 3 months after BCAS. Spatial working memory was assessed using an 8-arm radial arm maze at 3 months, although there was no significant difference between sham and BCAS animals. In the BCAS group, there were no overall significant alterations in dendrites and glutamatergic pre- and postsynaptic terminals compared to sham at either 1 month or 3 months. In the majority of mice (12 out of 16) there was no evidence of ischaemic neuronal damage at either 1 month or 3 months. However, in a subset of mice (4 out of 16), global hypoperfusion resulted in ischaemic neuronal damage in the CA1 region of the hippocampus (in 3 mice from the 1 month cohort and 1 mouse from the 3 month cohort). These mice exhibited focal dendritic loss in the same regions showing ischaemic neuronal damage, without changes in the synapse density. Overall, this study demonstrated that modest chronic cerebral hypoperfusion does not induce degeneration of dendrites and glutamatergic pre- and postsynaptic terminals in the CA1, apart from in the few animals with ischaemic neuronal pathology in this region, which coincided with a significant loss of dendrites. The second study focused on the long-term changes to glutamatergic pre- and postsynaptic terminals and axons in a model of focal ischaemia. Previous publications have shown that synaptic terminals are vulnerable within hours to days after ischaemic stroke, however, little is known about chronic synaptic changes. Focal ischaemia was induced with 15 minutes of middle cerebral artery occlusion (MCAO), followed by 3 months of recovery. This model results in a diffuse ischaemic lesion in the ipsilateral striatum. The transgenic line used for this study was generated by crossing TgSwDI mice, which produce progressive β-amyloid pathology, with mice expressing enhanced green fluorescent protein (eGFP) tagged onto the postsynaptic protein PSD95 (PSD95:eGFP). TgSwDI x PSD95:eGFP mice and their WT x PSD95:eGFP littermates, underwent MCAO surgery to determine if focal ischaemia resulted in long-term synaptic degeneration and whether these changes are exacerbated by concurrent β-amyloid pathology. Histological techniques were used to determine the volumes of ischaemic neuronal pathology and axonal pathology for each brain. These measurements were compared between WT and TgSwDI mice, and showed that there was no genotype effect on total volume of ischaemic neuronal pathology or axonal pathology. The densities of glutamatergic pre- and postsynaptic terminals were analysed with immunohistochemistry and expression of PSD95:eGFP, within the striatal ischaemic lesion and surrounding peri-lesion. There was a significant loss of glutamatergic pre- and postsynaptic terminals within the ischaemic lesion in both WT and TgSwDI mice, but there were no significant differences between these groups. Glial responses are a feature of vascular pathology and may be involved in synapse degeneration. In this study the levels of microglia/macrophages and astrocytes were increased in the lesion 3 months after MCAO, with evidence that microglia/macrophages levels were inversely correlated with the density of postsynaptic terminals. Overall, the results from this study demonstrated that brief focal ischaemia leads to long-term neuron and axon damage, loss of glutamatergic pre- and postsynaptic terminals, and glial responses within the ischemia lesion, however, the concurrent expression of TgSwDIAPP transgene did not exaggerate these changes. Finally, the third study investigated the impact of secondary neurodegeneration following focal ischaemia, and whether it is exacerbated by β-amyloid pathology. In patients with focal ischaemic damage or stroke, pathological changes have been found in remote brain regions that are connected to the ischaemic territory. In the current study, after 15 minutes of MCAO in mice there was long-term axon degeneration in the ipsilateral internal capsule, as well as axon degeneration and postsynaptic loss in the ipsilateral substantia nigra pars reticulata (SNR). In addition, microglia/macrophage and astrocyte levels were increased in the ipsilateral internal capsule and SNR. Interestingly, there was a larger increase in these glial markers in the internal capsule in the TgSwDI mice compared to the WT mice, although there were no signs of exaggerated axon degeneration in these mice. The results may indicate that white matter tracts are sensitive to glial responses and were exacerbated by concurrent TgSwDIAPP expression. Additionally, there was a small long-term increase in glutamatergic post-synaptic terminals in the ipsilateral thalamus of WT and TgSwDI mice, which may suggest that there is some synaptic rewiring in brain regions to compensate for synapse loss in other brain regions. The levels of glial cells were increased in the TgSwDI ipsilateral thalamus compared to the WT mice, which coincided with areas of β-amyloid immunostaining. Taken together, the results of this study indicate that focal ischaemia can stimulate long term secondary synaptic and axon degeneration, as well as small increases in synapse terminal density, in brain regions that are connected to the lesion site. There were no genotype effects on synaptic and axon degeneration; however, the presence of β amyloid did result in an even greater level of glial cells in the ipsilateral internal capsule and thalamus of TgSwDI mice after MCAO surgery, which may impact the integrity and function of this white matter tract. As part of the studies within the thesis, an alternative approach for inducing focal ischaemia was developed using Rose Bengal photothrombosis to generate a lesion in the cortex. This technique has been used for capturing real-time changes in the brain with multiphoton microscopy. Experiments were performed to optimise this method with the aim to measure dynamic synaptic changes in the presence of an ischaemic lesion and β amyloid with multiphoton microscopy. This study found that Rose Bengal photothrombosis caused large ischaemic lesions in the cortex, and in some cases the underlying subcortical structures, with variation and a lack of reproducibility between cases. Because of the challenges with using photothrombosis and multiphoton microscopy, the study design was changed to using MCAO and histological methods to measure synaptic changes, as described above. Overall, the studies in this thesis further support the hypothesis that the degree and type of cerebral blood flow reduction has an impact on the extent of synaptic and neuron degeneration. The results showed that modest global cerebral hypoperfusion was insufficient to cause reductions in synaptic and dendritic densities, indicating that in this model cognitive impairment occurs independently of synaptic loss. Focal ischaemia, however, did cause chronic synaptic loss within the lesion and remote brain regions, coinciding with glial responses and with evidence that postsynaptic loss in the lesion relates to the density of microglia/macrophages. Interestingly, the concurrent TgSwDIAPP expression did not exacerbate synapse and neuron degeneration, whereas it did increase the levels of glial cells in the ipsilateral internal capsule and thalamus. The data implies that in cases of chronic cerebral hypoperfusion, cognitive decline is not a result of glutamatergic synaptic degeneration. In patients with ‘mixed’ ischaemic and Alzheimer’s pathology, degeneration of glutamatergic synaptic terminals is driven by mechanisms related to cerebral blood flow changes, rather than β-amyloid. However, concurrent β-amyloid can result in exaggerated glial responses in brain regions distal from the lesion site. These studies demonstrate the long-term impact of brief or modest cerebral blood flow reductions on synapses and brain function. The results imply the need for adequate recognition, prevention and treatment measures which could help patients avoid the development of vascular cognitive impairment and dementia. Furthermore, this work suggests that while the presence of β-amyloid might contribute in some extent to glial responses, it has little impact on synaptic and neuronal damage. Therefore, the implications are that therapeutic intervention targeted at processes relating to ischaemia, rather than β-amyloid, would be more effective at alleviating synaptic and neuronal degeneration in cases of mixed pathology. Moreover, the studies indicated that glial changes are persistent features of cerebrovascular injury and can be exaggerated with multiple disease comorbidities. Future developments should focus on gaining a better understanding of this long-term immune response and how it influences brain function.
Keywords: synapses; blood flow reduction; dementia; β-amyloid protein